Summary Report: Sub-national food systems transformation decision supporting process to accelerate local food systems transformation implementation in Dong Thap and Son La until December 2025 - Huynh Thi, Tuyen Thanh; Nguyen, Quoc Minh; Pham Thi, Huong Mai; Duong, Thanh Thi; Dao, The Anh; Pham, Thi Hanh Tho; Tran, Van The; Truong, Thi Thu Trang; Bui, Thi Viet Anh; Truong Tuyet, Mai; Lundy, Mark M. (2025)
This report aims to summarize the sub-national Food Systems Transformation Decision Supporting (FSDS) process conducted in Dong Thap and Son La provinces to support Vietnam's National Action Plan implementation at provincial levels. Through collaborative efforts between national and provincial stakeholders, the process established Provincial Intersectoral Working Groups, conducted capacity-building training, developed food system profiles, and identified priority issues and resources. Key outputs include provincial implementation plans, guidelines for food system profile development and issue prioritization, and knowledge products. The participatory, multi-stakeholder approach demonstrates an effective model for translating national food systems policies into locally-relevant action at sub-national levels through evidence-based assessment and multi-sectoral coordination.